Being a ‘Real Boy’: The High School Experiences of Homosexual Men - Petrokaitis, Matas (Socialinė teorija, empirija, politika ir praktika, 2025)
The study examines the identity formation experiences of young men who do not conform to heteronormativity and who identify as homosexual within the context of secondary school. Based on social gender identity construction theories, the research seeks to explore how the ‘appropriate’ masculinity is constructed in the school environment and how it is experienced by those who do not conform to it. The aim of the study is to investigate how social agents in secondary school shape the male identity and how homosexual men experience ‘being different’. The research method is the three-stage mapping method of visual sociology. The interview transcript content analysis was performed by using the MAXQDA software, generating code trees. To ensure anonymity, transcripts and participant-created maps were de-identified. The study revealed that the ‘real boy’ standard at school is shaped by heteronormative expectations. As a result, young homosexual men, who are unable to conform to the established norms, have developed mechanisms of self-preservation. In doing so, they partially integrated into the heteronormative system, while simultaneously resisting it, despite facing pressure or even violence from parents, peers, or teachers.
Keywords: masculinity; homosexuality; gender stereotypes; heterosexualized norms